The Status and Challenges of Sustainable Intensification of Rice-Potato Systems in Southern China - Lu, Y.; Kear, P.; Lu, X.; Gatto, M. (Springer, 2021)
Potato is the world's largest non-cereal crop, occupying a position critical for global food security. In China, potato is the fourth largest crop adding to food security and incomes. The large population and unremitting reductions in arable land are the most critical root causes of China's food security problems. Hence, crop yield improvements and strategies to improve land use are at the forefront of solutions to increase China's food security. Maintenance of existing land resources while increasing crop yields, avoiding soil quality degradation and wastage of water are enduring problems that have long attracted widespread attention in many research fields. This article, analyzes and discusses the status and challenges to sustainable intensification of rice-potato rotation in southern China. Three significant findings were obtained in this paper, viz. availability of about 16 million hectares of suitable land for rice-potato intensification in southern China in 2016 are reported, several conservation agricultural practices with varying intensity and higher economic benefits in rice-potato rotation than rice-fallow, which may positively effects the environment. It was concluded that agricultural intensification with potato was an economically viable avenue along with good agricultural practices that minimize adverse environmental effects.